2011
DOI: 10.1002/cmdc.201100372
|View full text |Cite
|
Sign up to set email alerts
|

Development of Isoxazoline‐Containing Peptidomimetics as Dual αvβ3 and α5β1 Integrin Ligands

Abstract: Isoxazoline-containing peptidomimetics, designed to be effective α(v)β(3) and α(5)β(1) integrin ligands, were synthesized through an original procedure involving N,O-bis(trimethylsilyl)hydroxyamine conjugate addition to alkylidene acetoacetates, followed by intramolecular hemiketalization. To mimic the RGD recognition sequence, basic and acidic terminal appendages were introduced, and the final products were tested in cell adhesion inhibition assays. All the synthesized compounds proved to be excellent ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Moving from our previous experience in the field of highly stable and biologically active peptides containing β‐amino acids, including integrin ligands, we envisaged the opportunity to design new peptidomimetic α4β1 integrin antagonists containing the Amo α/β‐dipeptide scaffold. In this sense, we observed that the large majority of the peptidomimetic α4β1 ligands share common structural features: a α4‐targeting diphenylurea moiety at the N ‐terminus, a suitable spacer, and a C ‐terminal Asp or a mimetic containing a carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Moving from our previous experience in the field of highly stable and biologically active peptides containing β‐amino acids, including integrin ligands, we envisaged the opportunity to design new peptidomimetic α4β1 integrin antagonists containing the Amo α/β‐dipeptide scaffold. In this sense, we observed that the large majority of the peptidomimetic α4β1 ligands share common structural features: a α4‐targeting diphenylurea moiety at the N ‐terminus, a suitable spacer, and a C ‐terminal Asp or a mimetic containing a carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous potent anti-α5β1 integrin inhibitors 27,28,29,30 that could be modified with a linker and conjugated to Ab 38C2 giving anti-α5β1 chem-Abs. Initially, we focused on compound 1 27 (Figure 1), and synthesized an analogous compound 2 that possessed an alkyne function for introducing a linker enroute the Ab-PAs, 4 ’s, and chem-Abs 38C2- 4 ’s.…”
mentioning
confidence: 99%
“…Cell adhesion assay. In our previous experience, isoxazoline-based integrin ligands showed a strong potency towards α v β 3 and α 5 β 1 integrins, not affected by changing the alkyl group linked to position 3 18 . In designing this novel small library of peptidomimetics, alkyl chains were substituted by polyfunctionalized linkers including the triazole ring and amide, carbamate or ester moieties, that may create further interactions with the binding pocket.…”
Section: Resultsmentioning
confidence: 88%